Indo-Bangla Connectivity Projects and Its Geopolitical Implication - Khalid Saifullah (Universitas Muhammadiyah Malang, 2019)
Bangladesh and India are neighboring countries of south Asia sharing a huge border. India is eager to connect its north-east zone through Bangladesh. Again, Both China and USA have deep political interest in Bangladesh and Bay of Bengal. In this situation, Bangladesh has to consider connectivity as geopolitical game. So, granting connectivity projects with India whether it is beneficiary or harmful to Bangladesh is still debatable. If Bangladesh cannot balance both sides, Bangladesh might be the next shatterbelt. Again, Bangladesh has also chance to use connectivity as a tool of economic development. This paper aims to show the geopolitical context whether Bangladesh would be beneficiary or not.